Spiritualitas, Doa Dan Prestasi Belajar - Istiqomah, Nurul; Pebrian, Rio; Mutoharoh, Susi (BELAJEA: Jurnal Pendidikan Islam, 2018)
The purpose of this study is to examine aspects of prayer spirituality in the perspective of neuroscience and its implications for achievement. To see the relationship between the attitude of spirituality that is usually associated with prayer and endeavor, including business with the results obtained when done doing so. There is no connection between the brain and the activities of the owner of the brain because it is in the head and human activities are usually carried out in the outside area, but if you have studied the brain, especially neuroscience learning, then the body parts and what the owner does are interconnected. The results of the analysis mostly suggest that spirituality and learning achievement have relationships. The results of the study show that spirituality can be a predictor in ones learning achievement.